Exceedance probability of characteristic flows in Poland - Katarzyna Baran-Gurgul (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The goals of this paper are: to determine the empirical exeedance probability of the characteristic flows Qchar (SNQ, WNQ, NSQ, SSQ, WSQ, NWQ and SWQ) in Poland; to link the flows Qchar with quantiles Qp and to examine the relationship between the empirical exeedance probability of the flow Qchar from: Qp, the catchment area A and the gauging station elevation H.